Degenerative changes in the intervertebral joints of the cervical spine after anterior interbody fusion and intervertebral disc arthroplasty - Aleksandr S. Eliseev; Andrey E. Bokov; Sergey G. Mlyavykh (Хирургия позвоночника, 2023)
Objective. To study the effect of arthroplasty and anterior interbody fusion in the cervical spine on degenerative changes in the adjacent intervertebral joints. Material and Methods. A retrospective cohort study included 46 patients (22 with cervical total disc arthroplasy – CTDA, and 24 with anterior cervical discectomy and fusion – ACDF) with symptoms of cervical spondylogenic compression myelopathy and/or radiculopathy. The degree of degeneration of facet joints adjacent to the operated segments was evaluated 12 months after surgical treatment. Degenerative changes in the cervical spine were assessed using CT according to the Okamoto classification. Vidar Dicom Viewer 3.2 software was used to view images and evaluate intervertebral joints. Statistical processing was performed using IBM SPSS Statistics 23. Data were presented as median and 25th and 75th percentiles – Me [Q1; Q3]. Results. The mean age of patients in both groups was 47 [39; 52] years (Mann – Whitney U-test, p = 0.047). In the ACDF group it was 48 [42; 55] years and in the CTDA group – 42 [36; 52] years. Comparison of degenerative changes in the ACDF group before and after treatment (Wilcoxon analysis) showed a statistically significant difference in the cranial (p = 0.023), and caudal (p = 0.001) joints, with the progression of degeneration degree. In the CTDA group, no difference between pre- and post-treatment degeneration degree (Wilcoxon analysis) was found in either cranial joints (p = 0.157) or caudal joints (p = 0.161). Conclusion. Surgeries to stabilize spinal segments in degenerative diseases undeniably affect the development of the adjacent level syndrome. However, the use of endoprosthetic technology makes it possible to aggravate the degree of degenerative changes in the intervertebral joints of adjacent segments to a lesser extent.